Shorter and longer-term risk for non-fatal suicide attempts among male U.S. military veterans after discharge from psychiatric hospitalization. (November 2021) - Britton, Peter C.; Crasta, Dev; Bohnert, Kipling M.; Kane, Cathleen; Klein, John; Pigeon, Wilfred R.
Abstract: Although there are key differences in shorter-term (days 1–90) and longer-term (days 91–365) risk factors for suicide after discharge from inpatient psychiatry, there are no comparable data on non-fatal suicide attempts. Risk factors for non-fatal attempts in the first 90 days after discharge were compared with those over the remainder of the year to identify temporal changes in risk. Records were extracted from 208, 554 male veterans discharged from Veterans Health Administration acute psychiatric inpatient units from 2008 through 2013. Proportional hazard regression models identified correlates of non-fatal attempts for 1–90 days and 91–365 days; adjusted piecewise proportional hazards regression compared risk between these time frames. 5010 (2.4%) veterans made a non-fatal attempt, 1261 (0.60%) on days 1–90 and 3749 (1.78%) on days 91–365. Risk across both time frames was highest among younger veterans ages 18–59, and those hospitalized with a suicide attempt or suicidal ideation. It was lowest among those with a dementia diagnosis. Risk estimates were generally stable over time but increased among those with substance use disorders and decreased among those with sleep disturbance and discharged against medical advice. Estimates of some risk factors for non-fatal attempts change over time in the year after discharge and differ from those that change for suicide. Different preventive approaches may be needed to reduce shorter and longer-term risk for non-fatal attempts and suicide in the year after discharge. Highlights: There are limited data on shorter (1–90) and longer-term (91–365) risk factors for suicide attempts after discharge. Risk was highest among veterans who were between 18–59, were hospitalized after a suicide attempt, and had suicidal ideation. Risk was lowest among those with a dementia diagnosis. Risk increased over the timeframes among those with substance use disorders. Risk decreased over the timeframes among those with sleep disturbance and those who were discharged against medical advice.